2011
DOI: 10.1371/journal.pntd.0001199
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Sensitivity of Dengue Rapid Test Assays Is Significantly Enhanced by Using a Combined Antigen and Antibody Testing Approach

Abstract: BackgroundSerological tests for IgM and IgG are routinely used in clinical laboratories for the rapid diagnosis of dengue and can differentiate between primary and secondary infections. Dengue virus non-structural protein 1 (NS1) has been identified as an early marker for acute dengue, and is typically present between days 1–9 post-onset of illness but following seroconversion it can be difficult to detect in serum.AimsTo evaluate the performance of a newly developed Panbio® Dengue Early Rapid test for NS1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 30 publications
(41 reference statements)
13
101
1
3
Order By: Relevance
“…3C). Consistent with previous literature reports, the inclusion of the IgM line in the interpretation of positivity increased the overall sensitivity to Ͼ80% during this time period (40,41). Over time, the sensitivity of the NS1 line alone fell to 64% on days 4 to 7 p.s.o.…”
Section: Resultssupporting
confidence: 89%
“…3C). Consistent with previous literature reports, the inclusion of the IgM line in the interpretation of positivity increased the overall sensitivity to Ͼ80% during this time period (40,41). Over time, the sensitivity of the NS1 line alone fell to 64% on days 4 to 7 p.s.o.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies have demonstrated the benefits of combining NS1 antigen and IgM antibody results for the diagnosis of dengue infections (2,11,19). NS1 antigen is detectable by commercial ELISAs in the first 7 to 9 days of infection, and IgM antibodies are detectable only after 4 to 5 days of infection (7,11,12); combining NS1 and IgM results allows for dengue diagnosis throughout the normal temporal spectrum of patient presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid tests, often combining NS1 detection with an antibody test, are also available and have a reasonable window of detection. 24 …”
Section: Clinical Assessment and Laboratory Diagnosismentioning
confidence: 99%